2020
DOI: 10.4102/sajpsychiatry.v26i0.1471
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and coping strategies of undergraduate medical students at the University of the Free State

Abstract: Background: Medical studies place students at risk for burnout. Resilience enables students to cope with adversity. Students’ coping skills will ensure the well-being of future healthcare professisonals.Objectives: This study investigated resilience and coping among undergraduate medical students.Setting: Undergraduate students at the University of the Free State medical school.Methods: A cross-sectional study was performed. Quantitative data regarding resilience (Connor-Davidson Resilience Scale), coping stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 20 publications
(67 reference statements)
3
25
0
Order By: Relevance
“…In health personnel, a high level of resilience was found in physicians, nursing technicians, and obstetricians [ 11 ]. Similar positive attitudes towards the pandemic have been reported in several studies among university students in Jordania [ 16 ], China [ 17 ], Pakistan [ 18 ], and South Africa [ 19 ]. Considering military personnel, a national study of U.S. military veterans found that two-thirds of military personnel exposed to pandemic stressors exhibited a pattern of resilience [ 13 ], while a study of U.S. Air Force personnel found a high mean resilience score [ 20 ].…”
Section: Introductionsupporting
confidence: 82%
“…In health personnel, a high level of resilience was found in physicians, nursing technicians, and obstetricians [ 11 ]. Similar positive attitudes towards the pandemic have been reported in several studies among university students in Jordania [ 16 ], China [ 17 ], Pakistan [ 18 ], and South Africa [ 19 ]. Considering military personnel, a national study of U.S. military veterans found that two-thirds of military personnel exposed to pandemic stressors exhibited a pattern of resilience [ 13 ], while a study of U.S. Air Force personnel found a high mean resilience score [ 20 ].…”
Section: Introductionsupporting
confidence: 82%
“…Secondly, medical students show high levels of resilience, which positively correlates with adaptive coping strategies when facing a problem [45], and has been shown to prevent the development of anxiety, as well as post-traumatic stress disorder and depression [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is positively related to faculty students' personal burnout. Van der Merwe et al 43 confirm that students who use maladaptive coping strategies, like Substance Use, have decreased resilience to stress. Since high rates of substance abuse have frequently been reported among both medical students and health care professionals 44 , this result confirms that the deteriorating effect of this dysfunctional mechanism should be communicated more seriously at the university level and students taught to use more functional strategies instead.…”
Section: Discussionmentioning
confidence: 98%